The influence of climate change, site type, and disturbance on stand dynamics in northwest British Columbia, Canada - Nitschke, Craig (2012)
Stand and disturbance dynamics are key processes that need to be assessed along withclimate-species interactions if we are to better understand the impacts of climate change on species. In this study we investigated the biotic interactions (competition) between species, the influence of disturbance type, and changes in resource availability (moisture and light) on the response of six tree species to climate change in the northwest region of central British Columbia, Canada. Two ecological models were parameterized, linked together and coupled to climate change scenarios to explore the interactions between: (1) the response of species in the regeneration phase and (2) the role of disturbance, resource availability and competition on determining stand composition and productivity. Climate change was found to reduce soil moisture availability which resulted in a decline in regeneration potential for all species on dry sites and negative to neutral responses on sites with higher water availability. Following fire, stand dynamics and composition were modeled to undergo significant changes under the 2080s climate compared to current climate conditions on dry and mesic sites. Changes in stand dynamics under climate change were marginal following bark beetle disturbances. While significant changes to stand dynamics were found on dry sites, the presented results suggest that the sites with the highest moisture availability maintain the same general stand dynamics and composition following disturbances under climate change. This study highlights the need to consider species response to climate change in interaction with existing stand conditions, disturbance type, competition, resource availability, not just temperature and precipitation.